2004
DOI: 10.1038/sj.mp.4001593
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific association between bipolar affective disorder in women and GPR50, an X-linked orphan G protein-coupled receptor

Abstract: GPR50 is an orphan G protein-coupled receptor (GPCR) located on Xq28, a region previously implicated in multiple genetic studies of bipolar affective disorder (BPAD). Allele frequencies of three polymorphisms in GPR50 were compared in case-control studies between subjects with BPAD (264), major depressive disorder (MDD) (226), or schizophrenia (SCZ) (263) and ethnically matched controls (562). Significant associations were found between an insertion/ deletion polymorphism in exon 2 and both BPAD (P ¼ 0.0070), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
84
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 47 publications
5
84
0
Order By: Relevance
“…57 Sex-specific associations with schizophrenia have been reported for the catechol-O-methyltransferase gene 58 and several other genes. 59,60 It was also argued recently that sex may play a more important role in brain structure and psychiatric disorders than commonly acknowledged. [61][62][63] Our finding is consistent with this converging evidence.…”
Section: Discussionmentioning
confidence: 99%
“…57 Sex-specific associations with schizophrenia have been reported for the catechol-O-methyltransferase gene 58 and several other genes. 59,60 It was also argued recently that sex may play a more important role in brain structure and psychiatric disorders than commonly acknowledged. [61][62][63] Our finding is consistent with this converging evidence.…”
Section: Discussionmentioning
confidence: 99%
“…53 Sex-specific associations with schizophrenia have been reported for the catechol omethyltransferase gene 38 and several other genes. 54,55 It was also argued recently that sex may play a more important role in brain structure and psychiatric disorders than commonly acknowledged. [56][57][58] Our finding is consistent with this converging evidence.…”
Section: Discussionmentioning
confidence: 99%
“…A female-specific association between BPAD and/or SCZ has been previously observed in both GPR50 15 and CREB1. 36 However, we cannot definitively say that there is no effect in males because the 95% CIs of the ORs in the male groups overlap with those of the ORs in the female samples where the significance was observed, indicating that there is no significant difference between their respective ORs.…”
Section: Discussionmentioning
confidence: 71%
“…Thus, we deemed it necessary to test the hypotheses that GPR78 may be involved in the pathogenesis of BPAD, SCZ or both BPAD and SCZ, in which all affected individuals were grouped together, as it has been previously suggested that the two psychiatric illnesses may share susceptibility loci. 33,34 Similarly, owing to evidence of differences between males and females in the manifestation of psychiatric illness 35 and from findings of sex-specific association in the analysis of other candidate genes, 15,36 analysis was also carried out on samples separated on the basis of gender.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation